PEER LEARNING-BASED STRATEGY IN EFL READING CLASSROOM - Juang Kurniawan Syahruzah (Universitas PGRI Yogyakarta, 2016)
The intention of this study is to describe the effectiveness of peer learning in EFL reading classroom of English Department students of PGRI University. The comprehension analysis is intended by comparing the answer of EFL reading classroom students in reading exercises. In order to sequence the reading comprehension of the EFL reading classroom the pre-test and post-test of reading exercises are measured. The experiment of reading comprehension includes the recruitment of 40 students of EFL reading classroom, the training, and exercising of reading text in reading exercises. These students are all first-year female teacher training students at PBI-UPY and aged between 17 and 23. The measurement is compare with pre-test and post-test of reading exercises. Standard measurement is comparison of students answer in pre-test and post-test of reading exercises. The result of this research the students who passed the standard score improved from 37% in the preliminary data to 77% at the end of the research. It means that peer learning strategy improves students’ reading comprehension that was influenced by student’s factors (attention, interest and participation) and lecturer factors (choosing the material and managing classroom). Keywords: peer learning based, EFL, non-native reading comprehension